The moderating role of institutional quality on the financial development and foreign direct investment nexus: Evidence from East African Countries (EAC) - Mapendo, Joseph James (2025)
The study examines the effect of financial development measured by banking services and stock market size on FDI inflows, with the moderated role of institutional quality (Corruption, government effectiveness, and political stability) in East African countries. The FDI inflows in EAC have been challenging as the level that flows to this region has been declining. The attraction of this crucial foreign-based investment is essential in the economic development of this region due to its beneficial spillover effects. The study considers financial development a critical aspect that is pivotal in enhancing the host country’s investment climate. The study used panel data for twenty-six years, from 1995 to 2020. Similarly, the institutional FDI fitness, the Eclectic paradigm (OLI framework), and the Capital Market (currency areas) theories were employed to examine the relationship between banking services, stock market size, institutional quality, specified macroeconomic variables, and FDI inflows. The study has been governed by five objectives, which include investigating the influence of banking services on the level of FDI inflow, investigating the influence of stock market size on the level of FDI inflow, investigating the influence of institutional quality (Corruption, Government Effectiveness, Political stability) on the level of FDI inflow, investigating the moderating effect of institutional quality (Corruption, Government Effectiveness, Political stability) on the relationship between banking services and the level of FDI inflow, and investigating the moderating effect of institutional quality (Corruption, Government Effectiveness, Political stability) on the relationship between stock market size and the level of FDI inflow. Using the Feasible Generalized Least Squares (FGLS) estimator as the main model and the Panel Corrected Standard Errors (PCSE) estimator for a robustness check, the study findings reveal a significant relationship between financial development and FDI. Specifically, banking services positively influence FDI inflows to the EAC, implying that stronger, more efficient banking sectors can attract more foreign investment. This suggests that improving financial infrastructure, such as increasing credit availability, enhancing financial transparency, and ensuring regulatory stability, can boost investor confidence and capital inflows. As a result, policymakers in this region may prioritize financial sector reforms to stimulate economic growth through increased FDI inflows. On the other hand, the stock market size negatively impacts FDI. The negative impact of stock market size on FDI reveals that underdeveloped stock markets may signal limited capital market depth, which can deter foreign investors. This highlights the importance of developing and strengthening stock markets to enhance investor confidence, improve financial transparency, and attract more stable, long-term FDI. The findings reflect that foreign investors in EAC are more attracted by the banking sector when they need financial support to finance their growth and expansion strategies. Again, policymakers may need to focus on capital market reforms as part of a broader strategy to boost FDI inflows. The results further reveal that institutional quality in EAC hurts FDI inflows. The findings reflect that poor governance, legal uncertainty, and a lack of regulatory enforcement deter foreign investors. This suggests that improving institutional quality, such as strengthening the rule of law, reducing corruption, and enhancing regulatory effectiveness, is critical for attracting and sustaining FDI. Policymakers should prioritize institutional reforms to create a stable and predictable investment climate. Additionally, the moderated institutional quality has a dual effect on the investment process, either positively or negatively altering the impact of banking services and stock markets on FDI. The findings imply that strong institutions enhance the positive impact of banking services and mitigate the adverse effects of underdeveloped stock markets on FDI. This dual influence suggests that institutional quality acts as a key enabler for financial development to attract foreign investment effectively. Thus, policymakers should focus not only on financial sector reforms but also on strengthening institutional frameworks to maximize FDI inflows. However, the study has theoretical, practical, and policy implications regarding financial development and institutional quality practices for diverse parties, including investors, authorities, and scholars. The study suggests that to attract more FDI, EAC countries should pursue integrated reforms that develop both the financial sector through improved banking services and balanced stock market growth and institutional quality. Strong institutions enhance the positive effects of banking development and help manage the mixed influence of stock market size on FDI inflows. Therefore, policymakers should focus on strengthening governance, legal frameworks, and regulatory effectiveness alongside financial sector reforms to create a stable, transparent, and investor friendly environment that supports sustained foreign investment. Keywords: Financial development, foreign direct investment, institutional quality, banking size, stock market development, FGLS, PCSE. Subject Area: 0412-Finance, Banking and Insurance